An Account of Economic Thought in Mexico during the Independent and Reform Period (1824-1876) - Villalobos López, José Antonio (Iberian Journal of the History of Economic Thought, 2026)
The objective of this paper is to analyse and interpret the two main schools of economic thought that clashed in the Mexican Republic between 1824 and 1876. The study is developed using the historical method, adopting a hermeneutic paradigm and a qualitative approach. During this period, the country experienced marked political and social instability, which resulted in a lack of economic growth over a period of sixty years. In this context, two currents emerged that disputed the direction of the nation. On the one hand, the liberal school, based on the theories of Smith, Ricardo, Say, Mill and Bentham, represented in Mexico by José Luis Mora, Ignacio Ramírez “the Necromancer” and Guillermo Prieto. On the other hand, there was the protectionist school, based on the ideas of Colbert, List and Hamilton, with figures such as García Salinas, Estevan de Antuñano, Carlos de Olaguibel and Lucas Alamán. The liberals saw agriculture and mining as the engines of the economy, while the protectionists believed that the real impetus should come from national industry, protected and promoted by the state.
Keywords: economic doctrine; ideology; liberalism; Mexico; protectionism